2022
DOI: 10.1001/jamainternmed.2022.1262
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of the Incremental Value of a Coronary Artery Calcium Score Beyond Traditional Cardiovascular Risk Assessment

Abstract: IMPORTANCECoronary artery calcium scores (CACS) are used to help assess patients' cardiovascular status and risk. However, their best use in risk assessment beyond traditional cardiovascular factors in primary prevention is uncertain.OBJECTIVE To find, assess, and synthesize all cohort studies that assessed the incremental gain from the addition of a CACS to a standard cardiovascular disease (CVD) risk calculator (or CVD risk factors for a standard calculator), that is, comparing CVD risk score plus CACS with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 33 publications
(122 reference statements)
0
25
0
Order By: Relevance
“…It is noteworthy that none of the thirteen resources included estimates of effect for both benefits and harms. These might include the number of people correctly and incorrectly reclassified as high risk or low risk when CAC score is added to the traditional risk score [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that none of the thirteen resources included estimates of effect for both benefits and harms. These might include the number of people correctly and incorrectly reclassified as high risk or low risk when CAC score is added to the traditional risk score [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of CAC in primary prevention remains controversial due to the lack of direct evidence on its effectiveness in reducing CVD outcomes and limited evidence of clinical utility beyond that provided by current risk assessment tools [ 4 , 5 , 6 ]. Despite its strong prognostic ability as a stand-alone test, studies have found only modest prognostic value beyond traditional risk factors [ 7 ]. Adding CAC into CVD risk assessment also raises issues about cost-effectiveness and equity of access [ 4 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…High cholesterol [ 150 , 173 ] or hypertension, for example, are clearly upstream risk factors but may operate through the acceleration of cell aging [ 90 , 174 , 175 , 176 ]. Coronary calcium scans [ 177 ], on the other hand, are a downstream biomarker, but cell aging may be the driving force behind plaque buildup [ 178 ].…”
Section: Future Approaches To Cardiovascular Disease Interventionmentioning
confidence: 99%
“…In this issue of JAMA Internal Medicine , Dr Bell and colleagues report the findings of a meta-analysis demonstrating that addition of CACS to traditional CVD risk models was associated with improvement in model discrimination, with a pooled gain in C statistic of 0.036 (95% CI, 0.020-0.052)—a small but statistically significant finding of unknown clinical significance. The authors based their literature search on a prior systematic review that was used by the US Preventive Services Task Force for its 2018 guidelines, which concluded that there was insufficient evidence to recommend adding CACS to traditional risk models . Six studies were found to meet the study criteria for inclusion in the meta-analysis by Dr Bell and colleagues .…”
mentioning
confidence: 99%